ChemInform Abstract: Amino Functionalized Mesoporous Silica Decorated with Iron Oxide Nanoparticles as a Magnetically Recoverable Nanoreactor for the Synthesis of a New Series of 2, 4‐Diphenylpyrido[4, 3‐d]pyrimidines. Issue 48 (2nd December 2014) - Shadjou, Nasrin; Hasanzadeh, Mohammad
Abstract The advantages of the present method are high yields, simplicity, and easy work‐up.